Percutaneous transforaminal endoscopic surgery combined with mini-incision OLIF and anterolateral screws rod fixation vs. MIS-TLIF for surgical treatment of single-level lumbar spondylolisthesis - Zhou, Tianyao; Fan, Wenshuai; Gu, Yutong; Che, Wu; Zhang, Liang; Wang, Yichao (Frontiers in Surgery, 2023)
Objective Oblique lumbar interbody fusion (OLIF) has been used to treat lumbar spine spondylolisthesis. However, it usually needs posterior pedicle screws fixation for biomechanical stability, and possible posterior direct decompression for relieving neurologic symptoms. We use percutaneous transforaminal endoscopic surgery (PTES) combined with mini-incision OLIF and anterolateral screws rod fixation for surgical treatment of lumbar spondylolisthesis. The purpose of study is to evaluate the feasibility, efficacy and safety of this method compared with minimally invasive surgery-transforaminal lumbar interbody fusion (MIS-TLIF). Methods From July 2016 to May 2018, 65 patients of lumbar spondylolisthesis (L2-4) with neurologic symptoms were treated using PTES combined with mini-incision OLIF and anterolateral screws rod fixation (31 cases, group A) or MIS-TLIF (34 cases, group B) in this study. Operative duration, blood loss, incision length, fluoroscopy frequency and hospital stay are compared. Pre- and postoperative visual analog scale (VAS) pain scores of back and legs, Oswestry disability index (ODI), intervertebral space height, lumbar lordotic angle, operative segmental lordotic angle and complications are recorded. The fusion status is assessed according to the Bridwell’s fusion grades. Results The VAS score of back and leg pain, ODI significantly dropped after surgery in both groups (P<0.001). There was no statistical difference of back and leg VAS score, ODI between two groups except that back VAS scores in group A were significantly lower than that of group B immediately after surgery (P=0.000). Group A had significantly more intervertebral space height and operative segmental lordotic angle than group B postoperatively (P=0.022, P=0.002). 23 segments (74.2%) were grade I and 8 segments (25.8%) were grade II in group A, 20 segments (58.8%) were grade I and 14 segments (41.2%) were grade II in group B at 2-year follow-up (P=0.194). No difference was observed in complication rate between two groups (6.5% vs 5.9%, P=0.924). Conclusion The long-term clinical efficacy and complications rate of both groups are comparable. PTES combined with mini-incision OLIF and anterolateral screws rod fixation is a good choice of minimally invasive surgery for lumbar spondylolisthesis, which hardly destroys the paraspinal muscles and bone structures.